Basel III regulatory reforms and bank financial performance: Evidence from Nigerian deposit money banks - Abubakar, Aliyu; Abdullahi, Aminu; Suleiman, Hadiza; Abdullahi, Mairo (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2026)
Purpose: This study examines how Basel III regulatory requirements affect the financial performance of Nigerian Deposit Money Banks (DMBs). Methodology: The study used panel data on 11 listed banks from 2018 to 2024, excluding 2021, which the Central Bank of Nigeria designated a regulatory transition year, and employed a fixed-effects model with cluster-robust standard errors to address unobserved heterogeneity and serial correlation. Results and conclusion: The results show that Basel III liquidity requirements have a negative impact on the profitability of the Nigerian Deposit Money Banks, which means that the higher the liquidity buffers, the less the banks can lend and invest in more profitable activities. The Basel III implementation framework also considers the short-term costs of compliance and adjustment to the reforms. Capital adequacy, funding stability, and leverage requirements, however, do not have a significant impact on profitability, indicating that these regulatory requirements were not limiting factors in the study period. The study also reveals that the larger banks do better because of economies of scale, diversification, and better operational efficiency. The study finds that Basel III reforms have increased financial resilience and prudential discipline in the Nigerian banking sector, albeit at the cost of short-term profitability in liquidity regulation. Implication of findings: The findings highlight the trade-off between regulatory compliance and financial performance in emerging markets, suggesting that banks balance liquidity buffers with profitability goals.